Corn Brownies Making Entrepreneurship Training in The Turi Distric - Wasito Wasito; Dyah Hadi Novida; Ida Fitriani (Universitas Muhammadiyah Sidoarjo, 2018)
Community service programs in the form of Entrepreneurship training were carried out in Turi Village, Turirejo Village, Kedamean District, Gesik Regency on August 21, 2017. This activity is the flagship work program of the 2017 KKN management study program. The name of this activity is